Livros não ficcionais para crianças - Marcus Vinicius Rodrigues Martins (2021)
This PhD research aims to identify the degrees of hybridization of verbal, visual and graphic languages that promote expansions towards non-fiction works. The specific objectives are to map the theoretical and methodological studies on non-fictional books written in the respective languages: Portuguese, Spanish, English and French; investigate verbal and visual strategies for knowledge transmission, based on the use of poetic, artistic and aesthetic resources in the work; Identify how non-fictional books are organized to fulfill the functions of informing the reader and analyze the use of visual devices such as photography, maps and interpictorial resources. A methodology of expansion is adopted, with the organization and analysis of the corpus from the closest to the strictly non-fictional - that is, the dominant presence of the technical and scientific discourse - to the most immersed in a proposal that configures a hybrid discourse - contaminated with a literary language, with an aesthetic load and full of visual and plastic resources, in dialogue with the informative content. The corpora consists of academic and non-academic production on nonfiction books for children and nonfiction books of three collections, namely: personal collection and other researchers who study the editorial production focused on childhood; books from Bebeteca / NEPEI - GPELL / FAE / UFMG / Brazil; and, finally, books from the Research Group of Literary Literacy - Gpell / Ceale / FaE / UFMG. To this end, approximately 108 national and international books, that employ innovations in the field of nonfiction and dialogue with the areas of literature, design and the fine arts, were selected. The choice of works considered the following criteria: materiality, authorship, graphic design and the possible interactions between verbal and visual discourses. The research is justified by the few findings in Brazilian academic production in this area that problematize non-fictional books for children. This generates the ignorance, by teachers and reading mediators, of the formative potential of these books for childhood. The lack of reflection on these kinds of books also reverberates in the Brazilian publishing market, which deviates the functions of scientific dissemination by prioritizing the production of books with a strictly didactic character, which reduces scientific knowledge to school contents accompanied by unattractive activities for the kids. To theoretically support the research, studies from researchers from different geographical contexts and theoretical perspectives that focus on nonfiction for children were selected. We conclude that the expansion methodology has shown that both information and art have come together in non-fictional children's books. There are proposals with a higher incidence of a scientific and informative discourse, and also those that present a dialogue between several languages with artistic appreciation and that break the barrier between fiction and nonfiction.